Shrub expansion in maritime forest responding to sea level rise - Sward, Rheya; Philbrick, Abigail; Morreale, Jonah; Baird, Cora Johnston; Gedan, Keryn (Frontiers in Forests and Global Change, 2023)
Expansion of shrubs has been observed in a number of biomes and in response to diverse global change drivers. Noting shrub expansion in coastal forests affected by sea level rise, we began to monitor shrub populations in a transgressing loblolly pine forest in coastal Virginia. Forest study plots spanned a gradient of salinity and progression toward a ghost forest state, from high forest with a relatively closed canopy, to mid and low forest, where there were few remaining live canopy trees. Shrubs of the species Morella cerifera were censused for 3 years from 2019 to 2021. Shrub distributions were compared to distributions of the invasive grass Phragmites australis to test if competition with this invasive species played a role in the observed shrub distribution. Shrubs were most abundant in the mid forest, whereas P. australis was most abundant in the low forest, but we did not detect a negative correlation between changes in occupancy of P. australis and shrubs. Rapid growth of shrubs in the mid and high forest radically changed the forest understory structure during the study period. Basal area of shrubs in the mid and high forest tripled, and shrub occupancy increased from 45 to 66% in the high forest, with high patchiness between plots. A flooding event salinized the site in late 2019, during the study. Following the flood, soil porewater salinities in the low forest remained above levels known to cause mortality in M. cerifera for several months. We postulate that high salinity, rather than competition with P. australis, filters M. cerifera from the low forest, whereas moderate salinity in the mid and high forest favors M. cerifera growth and expansion. The increase in shrubs appears to be a hallmark of salt-affected maritime forest, with the shrub front occurring in advance of other indicators of transgression such as P. australis invasion.